Delay differential equations (DDEs) and its applications in pollution clean-up system - 315548 Tee, Chee Peng (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Sains (Matematik Industri)) - Universiti Teknologi Malaysia, 2006